DIGITAL PROJECT LIFECYCLE MANAGEMENT FROM THE PERSPECTIVE OF DATA INTELLIGENCE - Lunardeli, Stella (Journal of Interdisciplinary Debates, 2026)
Digital transformation has increased project complexity, demanding a re-evaluation of traditional management methods. This article presents a systematic literature review aimed at exploring how the integration of Big Data metrics and Artificial Intelligence (AI) can optimize estimation, risk mitigation, and success prediction throughout the digital project lifecycle. The research, focused on publications from the last five years (2020-2025), demonstrates that adopting a data-driven approach, aligned with Project Management Professional (PMP) practices, is fundamental for enhancing decision-making and performance. The findings indicate the emergence of predictive models based on Machine Learning (ML) which, by analyzing vast historical datasets of KPIs, ROI, and performance indicators, offer an improved capacity to anticipate deviations and optimize resource allocation. It is concluded that Data Intelligence is not merely a differentiator but a strategic imperative for the robust and effective management of projects in the digital economy.